DISPARITAS PUTUSAN HAKIM PENGADILAN AGAMA KABUPATEN MALANG TENTANG PEMBERIAN IZIN POLIGAMI (ANALISIS PERKARA NOMOR 3534/Pdt.G/2020/PA.Kab.Mlg dengan PERKARA NOMOR 0402/Pdt.G/2020/PA.Kab.Mlg) - Devi Juni Wardani; Dzulfikar Rodafi; Syamsu Madyan (Jurnal Hikmatina, 2021)
Religious Courts are judicial institutions that have products in the form of decisions and decisions. The decision is the result of deliberation by the panel of judges to decide a dispute case or there are two parties in dispute. For a decision, it is a decision issued by the judge as well, but there is no party to the dispute. Polygamy is included in a decision because there are disputing parties or problems. In this case, what are the guidelines or reasons used by judges in deciding cases, especially in cases of polygamy. Deciding a case does not necessarily just look at the lawsuit, but during the trial process, starting from case examination, prosecuting and proceeding to proceeding with the case. The examination of such cases can lead to disparities in judges' decisions. This disparity is what makes a decision different in terms of verdicts. By looking at how the evidence and witnesses are presented. So with this the judge can decide cases fairly and provide benefits to the parties. In accordance with the requirements of the decision, namely keeping away from harm and can provide legal benefits and certainty for justice seekers. Kata Kunci: Religious Courts, Decision, Polygamy, Disparity